A study of the creep-rupture behavior of HMPE ropes using viscoelastic-viscoplastic-viscodamage modeling. (15th August 2018) - Lian, Yushun; Zheng, Jinhai; Liu, Haixiao; Xu, Pengfei; Gan, Linlu
Abstract: Creep failure of HMPE ropes is a major concern for the application of HMPE ropes in deepwater moorings. Hence, the creep and creep-rupture behaviors of HMPE samples were systematically investigated by utilizing a special experimental set-up. The procedure and techniques for performing creep-rupture tests of HMPE samples were proposed in detail, which can be a reference for other sizes of synthetic fiber ropes. The test results illustrated that the completed creep-rupture curves include the primary, secondary and tertiary creep stages. To simulate the test results of HMPE samples, a viscoelastic, viscoplastic and viscodamage model was developed based on thermodynamics and a method for identifying the model parameters was proposed in detail. Moreover, the comparison of the model predictions with test data at different loading levels was performed and it showed satisfactory agreement, which means the present model can well simulate creep-rupture behaviors of HMPE samples. The present study helps to improve the understanding of creep-rupture behaviors of HMPE ropes for deepwater moorings. Highlights: Creep and Creep-rupture behavior of HMPE strands are systematically investigated by a special experimental set-up. The results illustrated that the creep-rupture curves of HMPE strands exist the primary, secondary and tertiary stages which shows that the present test method is effective. A coupled viscoelastic, viscoplastic and viscodamage model is developed within the framework of thermodynamics to describe the creep-rupture behavior of HMPE samples. The present model and the method of parameter identification are examined by comparing the prediction results with test data.